Worm-riding clam: description of Montacutona sigalionidcola sp. nov. (Bivalvia: Heterodonta: Galeommatidae) from Japan and its phylogenetic position - Goto, Ryutaro; Tanaka, Makoto (Zootaxa, 2019)
A new galeommatid bivalve, Montacutona sigalionidcola sp. nov., is described from an intertidal flat in the southern end of the Kii Peninsula, Honshu Island, Japan. Unlike other members of the genus, this species is a commensal with the burrowing scale worm Pelogenia zeylanica (Willey) (Annelida: Sigalionidae) that lives in fine sand sediments. Specimens were always found attached to the dorsal surface of the anterior end of the host body. This species has a ligament lithodesma between diverging hinge teeth, which is characteristic of Montacutona Yamamoto & Habe. However, it is morphologically distinguished from the other members of this genus in having elongate-oval shells with small gape at the posteroventral margin and lacking an outer demibranch. Molecular phylogenetic analysis based on the four-gene combined dataset (18S + 28S + H3 + COI) indicated that this species is monophyletic with Montacutona, Nipponomontacuta Yamamoto & Habe and Koreamya Lützen, Hong & Yamashita, which are commensals with sea anemones or Lingula brachiopods. This result suggests that host shifting across different phyla occurred at least twice in this clade.